Impak Amalan Kerohanian Bagi Mengatasi Kesunyian di Pusat Jagaan Warga Emas: The Impact of Spiritual Practice in Overcoming Loneliness at Elderly Care Centre - Mustaffa, Nurul Hidayawatie; Mat Akhir, Noor Shakirah; Hamjah, Salasiah Hanin (Afkar: Jurnal Akidah dan Pemikiran Islam, 2021)
Issues affecting senior citizens often come under the research radar amongst scholars; one of which is an internal crisis such as loneliness, anxiety, and depression either at home or in old folks’ homes. This research intends to study the spiritual practices like the daily routines of the elderlies residing in Darul Hanan Elderly Care Centre, Penang, as well as analyse their emotional impact, in overcoming loneliness, ensued from their spiritual practices. This is a qualitative study with a case study design. A total of 20 female senior citizens were interviewed. The selection of the study sample used is purposive sampling based on data saturation. The method applied was a semi-structured interview. Research data were analysed descriptively using Atlas.ti. The study finds that there are seven spiritual practices for the elderly at Darul Hanan Elderly Care Centre, Penang. They are daily and compulsory prayers (salat fard) in a congregation, night prayers (qiyamullayl), supplementary (sunat) practices, Qur’anic recitation, chanting praises for Allah (dhikr), chanting for forgiveness from Allah (istighfar), and attending religious lectures. The study also finds that there are 18 positive emotions of the elderly, such as fun, calm, happy, and relieved, after performing spiritual practices that are capable of overcoming loneliness. This makes the spiritual aspect an undeniable measure in overcoming loneliness for the elderly at old folks’ homes in ensuring the happiness of the elderly.